The impact of accepting new students with the zoning system on the right to children's education - Ganis Vitayanty Noor (Jurnal Hukum Volkgeist, 2020)
Education is a human right. Everyone has the right to receive educational rights without restrictions. Everyone has the right to get the education and level of education they will attend. The government has an education equalization plan with the issuance of the Minister of Education and Culture Regulation No. 14 of 2018. The Minister of Education and Culture mentioned above applies a zoning system. The Minister of Education and Culture does not rule out the possibility of impacts for prospective students who wish to continue their education. The problem is how the impact of the PPDB zoning system on education rights in Kajen Subdistrict, Pekalongan Regency. The approach method used is a sociological juridical approach method. PPDB has positive and negative impacts. According to researchers, PPDB is not in accordance with the right to education of children, due to restrictions, the gap in the quality of learning with the same level of difficulty of the National Examination and the same curriculum that applies nationally. Keywords: education rights, children, impact of zoning